O sentido da audição e as dificuldades auditivas atribuídas por um grupo de idosos - Sousa, Maria da Glória Canto de (2007)
Hearing is one of the human senses that contribute the most for social interaction. The hearing loss in the elderly, known as presbycusis, involves the decrease in speech intelligibility, restraining communication and the social life of the elder. Communicative limitations may lead to isolation, harming their social relations, and interfering in their quality of life. Purpose: Characterize the perception that old adults have of their own hearing, plus the identification of aspects involved in their process of communication. Method: This study was done through the use of a descriptive and exploratory research, having 40 students, being 34 females and 6 males, with ages varying between 61 and 88 years old, from an university called: Universidade Aberta à Terceira Idade (UATI), located in the city of Salvador, in the state university, named Universidade do Estado da Bahia (UNEB). Foi aplicado um questionário denominado Inventário Auditivo para Idosos (IAPI) e realizado o exame audiométrico nos sujeitos. A análise dos dados foi feita a partir das variáveis: sexo, faixa etária e pela computação das respostas dadas pelos indivíduos ao Inventário Auditivo para Idosos - IAPI (Mesquita, 2001).The subjects answered to a questionnaire and undergo audiometric tests. The data analysis was done considering the variables: gender, age and the computed answers for the questionnaire (Mesquita, 2001). Results: 37.5% of the subjects presented normal hearing and 62.5% hearing loss, being 30% symmetrical and 32.5% asymmetrical. Out of 25 subjects with hearing loss, only 04 (16%) were aware of it with a score for the questionnaire over 10 and 21 (84%) under 10. Related to gender, 8% of men and women scored over 10; 16% of men and 68% of women had scores over 10. There was a descending audiometric configuration in 88% of the subjects. Conclusion: In relation to age and degree of hearing loss, the greater the age, the greater the hearing loss, being proportionally higher for males than for females. It is fundamental to be in harmony with this population in order to contribute with our portion of knowledge and help the ones who are in our tomorrow´s place